SURVEI Anopheles spp. DI DESA ILAN BATU, KABUPATEN LUWU, PROVINSI SULAWESI SELATAN - Andi Arahmadani Arasy; Anis Nurwidayati (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2017)
Malaria is a mosquito-borne diseases, that caused by protozoan parasit Plasmodium spp. Indonesia is the second most affected region in South East Asia. This survey was aimed to identify the species diversity and biting activity of malaria vectors (Anopheles spp.) in Ilan Batu Village, Luwu Regency, South Sulawesi Province. The mosquitoes was collected by using the human landing collection technique and collecting mosquitoes resting on the wall of houses and cow barn. The results showed that there were three species of Anopheles i.e., An. barbirostris, An. vagus, and An. kochi. An. barbirostris was the species with the highest density. The value of man hour density (MHD) indoor and outdoor for An. barbirostris were 5.04 and 3.26 respectively.Based on the value of man hour density the mosquito An.barbirostris in Ilan Batu village were endophagic and endophilic